EXPLORING ATTITUDE TOWARDS PLAGIARISM AMONG RESEARCH SCHOLARS: A COMPARATIVE STUDY - Ashiq, Mehfooza (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Plagiarism is increasingly prevalent and major issue in scholarly writing, education and scientific world. Scholars are looking for speedy solutions when writing research papers, theses and dissertations. This study explores the impact of faculty and gender on attitude towards plagiarism of research scholars. This study was conducted at the University Level. For this study quantitative approach and survey as the design were adopted. Data was collected with the help of questionnaire developed by Martina Mavrinac, Gordana Brumini, Lidija Bilic-Zulle and Mladen Petrovecki (2010). Two-way ANOVA in this study revealed that faculty of research scholars had a significant impact on attitude towards plagiarism at the university level. However there was no significant impact of gender and interaction of gender and faculty of research scholars on attitude towards plagiarism at the university level. Based on these findings, it is recommended that research scholars should be made aware about plagiarism and ways of avoiding it. University administrators should frame the clear and strict policies for reducing the extent and influence of plagiarism.